2002
DOI: 10.1128/mcb.22.18.6592-6604.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone Proteins Abrogate Inhibition of the Human Papillomavirus (HPV) E1 Replicative Helicase by the HPV E2 Protein

Abstract: Human papillomavirus (HPV) DNA replication requires the viral origin recognition protein E2 and the presumptive viral replicative helicase E1. We now report for the first time efficient DNA unwinding by a purified HPV E1 protein. Unwinding depends on a supercoiled DNA substrate, topoisomerase I, singlestranded-DNA-binding protein, and ATP, but not an origin. Electron microscopy revealed completely unwound molecules. Intermediates contained two single-stranded loops emanating from a single protein complex, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 74 publications
3
65
0
4
Order By: Relevance
“…Consequently, disruption of the intimate E1:E2 complex on the DNA must occur before monomer E1:E1 interactions commence. Therefore, our results suggest that previous reports of HPV-11 E2 remaining bound to origin DNA during the assembly of E1 (Lin et al 2002) is a consequence of E2 being tethered at a distance from the E1 sites following disruption of the E1 · E2 association. In contrast, the close proximity of the E2-binding sites to the location of E1 assembly in BPV likely necessitates physical displacement of E2 from the origin.…”
Section: Regulation Of E1 Hexamerization By E2 and Atpsupporting
confidence: 53%
See 2 more Smart Citations
“…Consequently, disruption of the intimate E1:E2 complex on the DNA must occur before monomer E1:E1 interactions commence. Therefore, our results suggest that previous reports of HPV-11 E2 remaining bound to origin DNA during the assembly of E1 (Lin et al 2002) is a consequence of E2 being tethered at a distance from the E1 sites following disruption of the E1 · E2 association. In contrast, the close proximity of the E2-binding sites to the location of E1 assembly in BPV likely necessitates physical displacement of E2 from the origin.…”
Section: Regulation Of E1 Hexamerization By E2 and Atpsupporting
confidence: 53%
“…For BPV1, following the binding of additional E1 molecules, E2 is displaced from the viral origin (Lusky et al 1994;Sanders and Stenlund 1998). For HPV-11, it has been reported that E2 remains associated with the DNA during the assembly of E1 molecules, even though E2 might serve as a potential roadblock for extensive unwinding (Lin et al 2002). These differences raise several important questions.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Viral initiator proteins such as the simian virus 40 (SV40) large T antigen (T-Ag) and the papillomavirus E1 protein have long been known to melt their respective origins of DNA replication, as detected by oxidation with KMnO 4 (4,5,14,22,24,25). However, little information exists about which forms of these proteins execute melting, which parts of the polypeptide are responsible for the melting activity, and whether this process is DNA sequence dependent (5, 27).The E1 proteins from papillomaviruses are ϳ70-kDa polypeptides which, in addition to DNA melting activity, have DNA helicase activity (19,20,30,33,35,37,38,40) and also bind DNA. DNA binding by E1 is the result of two different DNA binding activities.…”
mentioning
confidence: 99%
“…The E1 proteins from papillomaviruses are ϳ70-kDa polypeptides which, in addition to DNA melting activity, have DNA helicase activity (19,20,30,33,35,37,38,40) and also bind DNA. DNA binding by E1 is the result of two different DNA binding activities.…”
mentioning
confidence: 99%